2017
DOI: 10.1007/s40273-017-0557-6
|View full text |Cite|
|
Sign up to set email alerts
|

Adjuvant Trastuzumab Therapy for Early HER2-Positive Breast Cancer in Iran: A Cost-Effectiveness and Scenario Analysis for an Optimal Treatment Strategy

Abstract: IntroductionClinical guidelines have recommended a 1-year trastuzumab regimen as standard care for early human epidermal growth factor receptor 2 (HER2)-positive breast cancer; however, this recommendation can have a dramatic impact on total drug expenditures in middle-income countries (MICs). We performed a cost-effectiveness analysis from the Iranian healthcare perspective to find an optimum duration of trastuzumab use in Iran.MethodWe compared four treatment strategies comprising chemotherapy and varying du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…We identified 22 EEs comparing adjuvant trastuzumab therapy with chemotherapy alone for HER2-positive EBC, published from year 2006 to 2018 (Table 1). As shown in Table 2, studies were mostly from high-income countries (HICs) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], while some [44][45][46][47][48][49] were from upper-middleincome countries (UMICs). About half [15,[28][29][30][31][32][33][34][35][36][37]44] were conducted and published as early as 2006 to 2009, which was within the early years of trastuzumab's market entry for HER2-positive early stage indication in 2006.…”
Section: General Study Information and Methodological Variationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 22 EEs comparing adjuvant trastuzumab therapy with chemotherapy alone for HER2-positive EBC, published from year 2006 to 2018 (Table 1). As shown in Table 2, studies were mostly from high-income countries (HICs) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], while some [44][45][46][47][48][49] were from upper-middleincome countries (UMICs). About half [15,[28][29][30][31][32][33][34][35][36][37]44] were conducted and published as early as 2006 to 2009, which was within the early years of trastuzumab's market entry for HER2-positive early stage indication in 2006.…”
Section: General Study Information and Methodological Variationsmentioning
confidence: 99%
“…More than half [28][29][30][31][32][33][34][35][36][37][38][39][40]44] have been published even before 2013 when the WHO reviewed its inclusion in the WHO Essential Medicines List [50]. In terms of methodology, majority of the studies [30][31][32][36][37][38][39][40][41][42][43][44][45][46][47][48][49] adopted cost-utility analysis, while some [28,29,[33][34][35] used cost-effectiveness analysis. All except two studies [5,10] used decision analytic Markov modeling technique.…”
Section: General Study Information and Methodological Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug costs associated with trastuzumab therapy will improve with the introduction of biosimilars, but a shorter duration may still improve patient’s quality of life and decrease the indirect costs associated with treatment such as cardiac monitoring, management of toxicity, and help free up resources for the ever increasing and large current demand for cancer care services. Analyses done have shown favorable cost-benefit for reducing the duration of trastuzumab specific to the region studied and this could have significant implications for improving access to care, especially in resource limited areas [ [47] , [48] , [49] , [50] ]. Additionally, the development of biomarkers to identify lower risk patients who may be ideal candidates for shorter durations of trastuzumab are needed.…”
Section: Discussionmentioning
confidence: 95%
“…Obviously, due to its shorter duration, 6 months of trastuzumab would cost less money compared with 12 months. In addition, a recent study from Iran indicated that 6 months of trastuzumab was a more cost-effective choice than 12 months, with far less incremental spending (8,826 vs. 18,588 pounds) (35). As a result, 6 months of trastuzumab might decrease the financial pressure on thousands of families using trastuzumab, and reduce their psychological burdens in the face of huge medical costs; this shorter duration of trastuzumab is more likely to be affordable for patients in low-and middle-income countries who lack sufficient medical funds.…”
Section: Discussionmentioning
confidence: 99%